2008
DOI: 10.1111/j.1528-1167.2007.01520.x
|View full text |Cite
|
Sign up to set email alerts
|

The three stages of epilepsy in patients with CDKL5 mutations

Abstract: SUMMARYInterestingly, the patients carrying a CDKL5 mutations causing a truncation of the catalytic domain tended to develop a more frequent refractory epilepsy than patients with mutations located downstream (4/6, 66.6% versus 1/6, 16%) although, these trends are not yet significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
175
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(193 citation statements)
references
References 24 publications
13
175
1
4
Order By: Relevance
“…Brain imaging in patients with CDKL5 mutations demonstrated cortical atrophy and white-matter hyperintensities. 53 In patients 3 and 5, MRI studies were normal and patient 6 had right tonsillar ectopia. Interestingly, patient 6 has also exotropia, which is frequently seen in patients with CDKL5 deficiency.…”
Section: Discussionmentioning
confidence: 93%
“…Brain imaging in patients with CDKL5 mutations demonstrated cortical atrophy and white-matter hyperintensities. 53 In patients 3 and 5, MRI studies were normal and patient 6 had right tonsillar ectopia. Interestingly, patient 6 has also exotropia, which is frequently seen in patients with CDKL5 deficiency.…”
Section: Discussionmentioning
confidence: 93%
“…Three stages for the course of the epilepsy in girls with CDKL5 mutations have been described and include an unusual, distinctive seizure type called hypermotor-tonic-spasms sequence (25,26).…”
Section: Other Genes For Epileptic Encephalopathies (Ee)mentioning
confidence: 99%
“…On the basis of this clinical presentation, the CDKL5-positive group has been assimilated to the Hanefeld early seizure variant of RTT [2]. Bahi-Buisson [7] has recently identified an epilepsy phenotype whose three-stage pattern begins with "early epilepsy", moves on to epileptic encephalopathy and ends with late multifocal and myoclonic epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…Given the small number of patients, genotype-phenotype correlation studies have been limited, but it has been suggested that mutations affecting the aminoterminal catalytic domain are associated with a more severe phenotype consisting of an earlier onset and intractable infantile spasms followed by late-onset multifocal and myoclonic epilepsy [7]. A more extensive knowledge of the currently restricted CDKL5 mutational repertoire might provide new clues concerning genotype-phenotype correlations, and analysing synthetic derivatives of particular mutants in functional assays might highlight new protein domains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation